The Relationship, Motor Ability and Social Behavior in Children of Age 4-6 Years - Bano, Elton; Ikonomi, Edison; Muka, Enkelejda (Arena-Journal of Physical Activities, 2019)
The purpose of the study is to understand the relationship between the motor and social ability after the gymnastic program intervention in preschool children. The children have their needs to move and to do exercises. They should exercise everyday to coordinate limbs and body muscles to move in the best way their body. This is one of the reasons why physical activity represent an essential part of the children education program.Methods.For the realization of our study, have selected 60 children from four Tiranaâ€™s preschools city, age 4 to 6. The children are separated in two equal groups.Collected data begin, middle and in the end of tests and questionnaires were under a statistical processing by IBM SPSS package, version number 22. T-test is used to see if there are significant changes between control and experiment group skills along the tests phases.Pearsonâ€™s Product-Moment coefficients is used to evaluate all the relations between dependent variables.Results.Dynamic balance skills has a negative direction correlation with social action. (r= -.36**, p=.00); social independence (r= -.48**, p=.00), and general social behavior evaluation (r= -.37**, p=.00). Static balance skill has a positive direction correlation with social interaction (r=.41**,p=.00); social action(r=.37**, p=.00); social independence (r=.39**, p=.00) and general social behavior evaluation (r=.11**, p<0.01).Conclusions.Study results shows that gymnastic programÂ has an impact in motor abilities education and development, but this impact in not the same in all abilities.